2011
DOI: 10.1099/mic.0.052357-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential stringent control of Escherichia coli rRNA promoters: effects of ppGpp, DksA and the initiating nucleotides

Abstract: Transcription of rRNAs in Escherichia coli is directed from seven redundant rRNA operons, which are mainly regulated by their P1 promoters. Here we demonstrate by in vivo measurements that the amounts of individual rRNAs transcribed from the different operons under normal growth vary noticeably although the structures of all the P1 promoters are very similar. Moreover, we show that starvation for amino acids does not affect the seven P1 promoters in the same way. Notably, reduction of transcription from rrnD P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The seven rRNA operons are regulated by the stringent response, and, when levels of ppGpp are high, transcription of the rRNA is repressed. [41] However, in ΔrelA this inhibition does not occur and levels of stable rRNA have been shown to be ∼2- to 10-fold higher than that of a relA + strain in similar conditions [46][50]. Within colony biofilms, we found that both 23 S and 16 S RNA expression was ∼2-fold higher in ΔrelA than wild-type during carbon source transitions at FC OD600  = 14 (Figure S4, Table S5).…”
Section: Resultsmentioning
confidence: 83%
“…The seven rRNA operons are regulated by the stringent response, and, when levels of ppGpp are high, transcription of the rRNA is repressed. [41] However, in ΔrelA this inhibition does not occur and levels of stable rRNA have been shown to be ∼2- to 10-fold higher than that of a relA + strain in similar conditions [46][50]. Within colony biofilms, we found that both 23 S and 16 S RNA expression was ∼2-fold higher in ΔrelA than wild-type during carbon source transitions at FC OD600  = 14 (Figure S4, Table S5).…”
Section: Resultsmentioning
confidence: 83%
“…The explanation for why (p)ppGpp is not needed may lie in the observation that nucleotide levels drop significantly when phosphate is depleted from the growth medium. At the rrnB P1 promoter and other stringently regulated rRNA promoters, Eσ 70 forms unstable open complexes, which are stabilized by binding of initiating nucleotides (iNTPs) and destabilized by DksA and (p)ppGpp (Gaal et al ., 1997; Barker et al ., 2001; Murray et al ., 2003; Murray and Gourse, 2004; Paul et al ., 2004b; Kolmsee et al ., 2011). A higher concentration of iNTP is required for transcription initiation at rrnB P1 in the presence of DksA than in its absence (Paul et al ., 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…Because nucleotide levels drop during phosphate starvation, the decreased availability of nucleotides in combination with destabilization of open complexes by DksA may reduce transcription initiation, eliminating the requirement for (p)ppGpp. Because most other rrn promoters form similarly unstable open complexes limited by iNTP concentrations, this mechanism of regulation is likely to be shared and not particular to rrnB P1 (Gaal et al ., 1997; Barker et al ., 2001; Murray et al ., 2003; Murray and Gourse, 2004; Paul et al ., 2004a; Kolmsee et al ., 2011). …”
Section: Discussionmentioning
confidence: 99%
“…This is manifested in the inhibition of production of the protein-synthesis system that is translation components: rRNA, r-protein and tRNA (1,2). The promoter initiating the expression of one of the seven rRNA operons in E. coli, rrnB P1, has been extensively studied and is currently one of the best characterized bacterial promoters (2325). Promoters initiating the synthesis of tRNA (another class of stringently controlled RNA) are far less studied in comparison to rrnB P1; however the mechanism underlying their inhibition during the stringent response was proposed to be similar (26,27).…”
Section: Introductionmentioning
confidence: 99%